ANALYSIS OF APPROACHES TO ASSESSING THE ECONOMIC COSTS ASSOCIATED WITH THE TIME PARAMETERS OF URBAN TRANSPORT SYSTEMS FUNCTIONING - V. V. Donchenko; R. V. Filippova (Вестник университета)
The directions of economic assessment of the costs associated with the time of transport movements of the urban population have been described. It has been shown, that solving the problem of improving the reliability of urban transport leads to saving passengers` time and the possibility of using the resulting savings in a more productive way, therefore, the calculation of the cost estimate of the change in travel time can be taken into account when choosing to implement a particular transport project, to assess the costs and results of public investment or regulatory impacts. A model of economic efficiency evaluation of transport projects, based on accounting of reduction in average travel time of urban population and improving the reliability of transport correspondences of urban transport has been proposed.